2020
DOI: 10.1093/ofid/ofaa439.1588
|View full text |Cite
|
Sign up to set email alerts
|

1406. Comparison of Clinical Presentations and Burden of Respiratory Syncytial Virus in Infants Across Three Distinct Healthcare Settings

Abstract: Background Respiratory syncytial virus (RSV) accounts for the majority of lower respiratory tract illnesses in hospitalized infants. In the U.S., RSV hospitalizations are well characterized; yet, emergency department (ED) and outpatient (OP) visits are underrecognized. We evaluated the burden of RSV across three distinct healthcare settings during one respiratory season. Methods From 12/16/19-4/30/20, we conducted a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Studies on S&S of RSV in the pediatric population (25 studies) took place in both community and clinical settings, and S&S were reported by both caregivers (six studies) 19 , 20 , 21 , 39 , 40 , 41 and clinicians (22 studies) 19 , 20 , 21 , 26 , 27 , 28 , 29 , 34 , 35 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ; we analyzed and present these two sets separately. In addition, two publications presented clinician‐reported S&S in the intensive care unit (ICU).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies on S&S of RSV in the pediatric population (25 studies) took place in both community and clinical settings, and S&S were reported by both caregivers (six studies) 19 , 20 , 21 , 39 , 40 , 41 and clinicians (22 studies) 19 , 20 , 21 , 26 , 27 , 28 , 29 , 34 , 35 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ; we analyzed and present these two sets separately. In addition, two publications presented clinician‐reported S&S in the intensive care unit (ICU).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies presented S&S reported by caregivers of children with RSV initially and primarily treated in the outpatient setting (Table S2 ). 20 , 21 , 39 , 41 All four studies were prospective and enrollment ranged from 361 to 923 children. One of these studies reported solely on wheezing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations